Analysis of A RCC Framed Structure with Shear Wall with and Without Bracing System Using Analysis Tool - Chuleshwar Prasad; K Divya; Pradeep Nirmal (International Journal of Scientific Research in Civil Engineering, 2025)
The seismic performance of reinforced cement concrete (RCC) shear walls with and without steel bracing is thoroughly examined in this thesis, with an emphasis on buildings situated in Seismic Zone V, which is defined by the Indian seismic code as having a high seismic hazard and a zone factor of 0.36. Two distinct models were used for the analysis: a standard RCC shear wall without bracing and an RCC shear wall integrated with steel bracing. With soil type III (soft soil) as the foundation condition, both models underwent comparable static and dynamic analyses. By comparing crucial metrics such base shear, story drift, overturning moment, and shear force, the main goal was to evaluate how well steel bracing worked with RCC shear walls.
Keywords: ETABS; maximum story displacement; seismic analysis; shear force; Shear wall; steel bracings